Diversifikasi Olahan Berbasis Ikan Hasil Tangkapan Kelompok Nelayan Berkah Bersama di Desa tumbang Nusa: Diversification of Fish-Based Products from the Catch of the Berkah Bersama Fishermen's Group in Tumbang Nusa Village - Yanti, Elyta Vivi; Indrayanti, Asro Laelani; Tangkasiang, Yos Andy; Aini, Ajeng Nur; Rusmiyanti, Rusmiyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Tumbang Nusa Village is a government area located in Jabiren Raya Subdistrict, Pulang Pisau Regency. Based on its governmental structure, Tumbang Nusa Village is led by a Village Head. The village has four neighborhood associations (RT), and the main livelihood of Tumbang Nusa Village's residents is traditional fishing. The fish caught include gabus, patin, toman, and kerandang. Through this village empowerment program, one economically productive community group is involved, namely the Bekah Bersama fishermen's group. The fishing group involved consists of women who work as fishermen daily, selling their catch as fresh fish. This often causes losses for the fishermen because the fresh fish does not always sell out, so they have to bring it back to be salted and dried. This activity introduces fish-based product diversification. Women fishermen are taught skills to make processed products such as fish balls, fish nuggets, and fish floss, and are also trained in packaging these products. The group of women fishermen responded positively to the technological innovations provided. All members of the group have practiced making fish balls, fish nuggets, and fish floss, as well as packaging the products. However, there is still untapped local potential, including establishing links between fishing activities, to provide a circular economy that benefits the community of Tumbang Nusa Village.